2010
DOI: 10.1159/000294191
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Genetic and Genomic Information: Health Literacy and Numeracy Considerations

Abstract: Genomic research is transforming our understanding of the role of genes in health and disease. These advances, and their application to common diseases that affect large segments of the general population, suggest that researchers and practitioners in public health genomics will increasingly be called upon to translate genomic information to individuals with varying levels of health literacy and numeracy. This paper discusses the current state of research regarding public understanding of genetics and genomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
205
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(227 citation statements)
references
References 111 publications
13
205
4
5
Order By: Relevance
“…Unrealistic hopes may needlessly predispose patients and families to greater distress when hopes for sequencing results are inevitably unmet. Poor health literacy and numeracy, 22 unfamiliarity with genetics terminology and patterns of inheritance, 23 and inevitable shifts in interpretation and return of results with advances in genomic medicine 24,25 complicate the communication of strengths and limitations of genomic sequencing. Taking into account patients' level of illness uncertainty and perceived resources could inform the development of guidelines for provider communication by helping providers ascertain patients' frame of reference for their hopes.…”
Section: Discussionmentioning
confidence: 99%
“…Unrealistic hopes may needlessly predispose patients and families to greater distress when hopes for sequencing results are inevitably unmet. Poor health literacy and numeracy, 22 unfamiliarity with genetics terminology and patterns of inheritance, 23 and inevitable shifts in interpretation and return of results with advances in genomic medicine 24,25 complicate the communication of strengths and limitations of genomic sequencing. Taking into account patients' level of illness uncertainty and perceived resources could inform the development of guidelines for provider communication by helping providers ascertain patients' frame of reference for their hopes.…”
Section: Discussionmentioning
confidence: 99%
“…Complexity and uncertainty will be guiding principles in genomic medicine, and providers and the public must know how to deal with them-conceptually and practically, as when making decisions about treatment and management. Complexity and uncertainty will compound the already well-documented challenges related to the public's understanding of risk [13,14].…”
Section: Objectives For Public Genetic Literacymentioning
confidence: 99%
“…Studies suggest that health literacy may impact the understanding of personal genomic risk (Lea et al, 2011). For example, it has been reported that women with lower health literacy recalled less information about a genetic test to predict breast cancer recurrence (although participants in these studies did not actually undergo genetic testing) (Lillie et al, 2007;Brewer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic literacy refers to one's knowledge and appreciation of basic genetic (and, in the modern context, genomic) principles, as they inform personal decision making and underlie effective participation in public debates on genetic or genomic issues (McInerney, 2002;Bowling et al, 2008). Some studies have reported low levels of public understanding of genetic concepts (e.g., location of genes) and applications (e.g., newborn screening), although participants displayed familiarity with genetic terminology (Lanie et al, 2004;Miller, 2004;Catz et al, 2005;Lea et al, 2011). In contrast, other studies have shown some public understanding of genetic concepts and genetics research, such as the meaning of a reported genetic association (Bates et al, 2003;Miller, 2004;Levitt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%